Computer problem solver (cops): a better understanding of problem solving in computer programming - Sadjirin, Roslan; Md Raus, Ikhsan; Noradzan, Haslinda; Alias, Nursyahidah; Ismail, Nor Zalina; Abd Aziz, Mohd Norafizal; Abd Aziz, Muhd Eizan Shafiq; Zakariah, Zazaleena; Hussain, Fazlin Marini; Ismail, Siti Nurbaya; Hashim, Norhafizah (University Teknology MARA Pahang, 2011)
The introduction course to computer programming is considered one of the most difficult courses by Computer Science students in Universiti Teknologi MARA Pahang (UiTM). The students' results for every semester in the Computer Programming course is always average. In order to enhance understanding of programming concepts and the skills in problem solving, an improvisation of the teaching and learning method is introduced and implemented on the first year students of UiTM Pahang. Therefore, this paper presents the introduction of the teaching and learning method called Computer Problem Solver (CoPS) for the teaching and learning of the Computer Programming course to the first year computer science students in their of UiTM Pahang